Relations Between Aortic Stiffness and Left Ventricular Mechanical Function in the Community - Bell, Vanessa (J Am Heart Assoc, 2017)
BACKGROUND: Aortic stiffness impairs optimal ventricular–vascular coupling and left ventricular systolic function, particularly in the long axis. Left ventricular global longitudinal strain (GLS) has recently emerged as a sensitive measure of early cardiac dysfunction. In this study, we investigated the relation between aortic stiffness and GLS in a large community‐based sample. METHODS AND RESULTS: In 2495 participants (age 39–90 years, 57% women) of the Framingham Offspring and Omni cohorts, free of cardiovascular disease, we performed tonometry to measure arterial hemodynamics and echocardiography to assess cardiac function. Aortic stiffness was evaluated as carotid–femoral pulse wave velocity and as characteristic impedance, and GLS was calculated using speckle tracking–based measurements. In multivariable analyses adjusting for age, sex, height, systolic blood pressure, augmentation index, left ventricular structure, and additional cardiovascular risk factors, increased carotid–femoral pulse wave velocity (B±SE: 0.122±0.030% strain per SD, P<0.0001) and characteristic impedance (0.090±0.029, P=0.002) were both associated with worse GLS. We observed effect modification by sex on the relation between characteristic impedance and GLS (P=0.004); in sex‐stratified multivariable analyses, the relation between greater characteristic impedance and worse GLS persisted in women (0.145±0.039, P=0.0003) but not in men (P=0.73). CONCLUSIONS: Multiple measures of increased aortic stiffness were cross‐sectionally associated with worse GLS after adjusting for hemodynamic variables. Parallel reductions in left ventricular long axis shortening and proximal aortic longitudinal strain in individuals with a stiffened proximal aorta, from direct mechanical ventricular‐vascular coupling, offers an alternative explanation for the observed relations.